Substituted piperazines as nootropic agents: 2- or 3-phenyl derivatives structurally related to the cognition-enhancer DM235. Issue 8 (15th April 2015) - Guandalini, Luca; Martino, Maria Vittoria; Di Cesare Mannelli, Lorenzo; Bartolucci, Gianluca; Melani, Fabrizio; Malik, Ruchi; Dei, Silvia; Floriddia, Elisa; Manetti, Dina; Orlandi, Francesca; Teodori, Elisabetta; Ghelardini, Carla; et al.
Graphical abstract